P080 An embedded pathway to mandibular advancement splint (MAS) construction in a tertiary hospital reduces barriers to care for low-income individuals. (7th October 2021) - Lim, B; Yap, T; Lim, M; Gikas, A
Abstract: Introduction: The aim of this study was to report the outcomes of patients referred within and to a tertiary hospital dental unit for subsidised construction of a MAS over a 5-year period. Methods: Medical records of patients referred from 2015–2020 were examined for reason for referral, details of diagnosis, pathway to diagnosis, treatment, compliance, clinician-reported and lab-based outcomes and follow-up reviews. Results: One hundred patients referred from: The Hospital Sleep Unit 40, other Tertiary Hospitals 27, Private Sleep Clinics 13, Medical GPs 10. 76 patients were confirmed health care card holders. 30 patients did not proceed for reasons of cost or poor oral health. 59 patients were newly fitted with a MAS (27F, 32M), 17 severe, 21 moderate, 17 mild OSA, mean age 52.9(+13.9) years, BMI 30.2(+6.3) kg/m2, ESS 11.4(+5.3). 22 of 36 patients with serial ESS scores had excessive daytime sleepiness upon initial presentation. 15/22(68%)(p<0.005) of patients had resolution of their excessive daytime sleepiness following MAS wear. 8/15(53%) of patients had a subsequent AHI <50%. 33 patients (56%) continued MAS wear, mean follow-up time 13.8(±14.6) months with an average of 5.8(+3.0) visits. 6 were lost to follow up, 20 patients (33%) ceased MAS wear with 10(50%) of these stopping because routine dental treatment affected the device fit or discomfort later developed. Conclusion: Subsidised expert construction of MAS embedded in a tertiary hospital is a well-utilised and effective service which reduces barriers for patients. The referrals to this service appear to be appropriate, with most patients proceeding to MAS construction.